Hands-on projects as a kinesthetic strategy to foster English acquisition. (2024)
In many countries of the world, the concept of Neurodiverse has gained more significance over the years. Therefore, this research was applied in a private institution in Medellín, Colombia, for sixth/seventh graders with neurodiversity because it is a context that is involved with the process of students with educational needs. However, the institution still tries to train teachers to apply the appropriate strategies to address this issue. The purpose was to describe the results of a hands-on project as a kinesthetic strategy in vocabulary acquisition in neurodiverse English learners. This research follows an action research method. To recollect the data, a semi-structured interview with open questions and journals was developed for lesson planning and to reflect classroom development and focus groups, which included open questions. This research found that contextualized learning, kinesthetic strategies, and learning styles are important in the English learning process. This study concluded that external factors (social, family, and school context) and internal factors (diagnosis and learning styles)affect students' learning process regarding participation, demotivation, scores, and social interaction, which can affect students' performance. Moreover, hands-on projects as kinesthetic strategies can foster the acquisition of English as a foreign language by accommodating diverse learning styles.